Особливості розвитку конфлікту в Нагірному Карабасі - Багірова, Вюсала Елмас Кизи (ЧНУ, 2021)
This master's thesis is presented for defense in the specialty "International Relations" at the Yuri Fedkovych National University of Chernivtsi
Магістерська робота
Keywords: Міжнародні відносини, конфлікт, Нагірний Карабах